Mathematical Modelling of an Unmanned Aerial Vehicle - Chong, Chiew Choy (2005)
This thesis presents the results of a study on the development of a mathematical model of the flight dynamics of a small-scaled aircraft. The aircraft, due to its small size has the potential to be converted to an unmanned aerial vehicle (UAV). A mathematical model of an aircraft flight dynamics can be derived through wind tunnel testing or Computational Fluid Dynamics (CFD) analysis. But the work presented in this study develops an alternative method by means of flight testing. The method shows that by proper analysis of the data from sensors that measure the aircraft state variables such as pitch angle, altitude, speed, a profile of the aircraft flight dynamics can be deduced. it is expected that the results h mth is study will benefit projects which interest is to convert existing flyable aircraft to be an UAV, such as the Composites Technology Research Malaysia (CTRM) project in Eagle Airborne Reconnaissance Vehicle (ARV) System. In this study, a small-scaled remote-controlled plane was equipped with onboard sensors and a data logger. A software program has been written for this project which intedaced the data-logging system, with a computer aided engineering (CAE) software MATLAB and its toolbox SIMULINK. Using the program developed, a profile of the aircraft longitudinal motion was collected through a series of flight tests. It was found that the aircraft longitudinal dynamics developed can be represented as a simple second order transfer function equation. Using the correlation coefficient method, it was found that 99.5% of the variability in short period flight test result is explained by the simulation result while 87.5% of the variability in Phugoid flight test result is explained by the simulation result. The results and method proposed in this study helps to re-create the flight dynamic characteristics of the small-scaled aircraft through flight simulation, which will be important for such work as control law determination in the future.